Thailand : Financial Sector Assessment Program; Technical Note; Fixed Income Markets. (IMF Staff Country Reports; Country Report ;, 2009)
This technical note focuses on fixed income markets for Thailand. The note recommends that Thailand should begin an orderly transition from merit-based regulation of corporate issuers and institutional investors to a disclosure-based regulatory system that opens the debt market to a larger and more diverse pool of corporations. A series of regulatory changes should be considered, including removing the limitations on below investment grade debt offerings, expanding the size of private placement offerings, and reducing the regulatory burdens on issuers of short-term commercial paper.